Overview of Patients with Hypertensive Heart Disease at the Cardiology Clinic of the Family Medical Center Hospital in 2020 - Didi Kurniadhi; Marshell Tendean; Karek Roberto Bernardi (Jurnal MedScientiae, 2022)
Hypertensive heart disease is a condition of changes in heart structure and function due to chronic hypertension, the term hypertensive heart disease ultimately includes conditions such as left ventricular hypertrophy, systolic heart failure, diastolic or both, irregular heartbeat and coronary heart disease. This study aims to describe the characteristics of patients with hypertensive heart disease such as sociodemographic descriptions such as age, gender, clinical manifestations, management including the type of drug given and the amount of drug given, as well as comorbidities in patients with hypertensive heart disease at the Cardiology Clinic of the Family Medical Center Hospital. 2020. The age group of patients with hypertensive heart disease is 56-65 years (36%), sex is dominated by women (55.8%), the majority of patients with hypertensive heart disease have clinical manifestations of LVH without heart failure (51.2%) , beta blockers were the most frequently administered drugs (72.2%), 3 types of drugs were the most frequently administered drugs to patients (33.8%), and diabetes was the most common comorbidity in patients (22.7%). Early screening and treatment of hypertension is very necessary to prevent the development of hypertension into hypertensive heart disease.